The evaluation of energetic and exergetic performances of solar air heater using transverse wire rib roughness with various gaps - an experimental study - Dilbag Singh Mondloe; Harish Kumar Ghritlahre; Gajendra Kumar Agrawal (Journal of Engineering and Applied Science)
Abstract This paper presents an experimental investigation into the performance of solar air heaters using transverse wire ribs with various gap configurations (Ng = 1, 2, 3, 4, and smooth). The study was conducted under diverse outdoor meteorological conditions in Jagdalpur, India. The key parameters utilized were mass flow rates (ṁ = 0.01891–0.03937 kg/s), relative roughness height (e/D = 0.043), and relative roughness pitch (p/e = 10). The results demonstrate that energetic efficiency (ηI) increases with mass flow rate, reaching the maximum of 83.5% for Ng = 2 at ṁ = 0.03937 kg/s. The exergetic efficiency (ηII) was obtained to improve with higher solar irradiance, elevated temperatures, and lower relative humidity, reaching a maximum of 3.67% for Ng = 2 and ṁ = 0.02889 kg/s. Moreover, the highest instantaneous thermal efficiency improvement factor (TEIF) for Ng = 2 was 13.42 at ṁ = 0.01891 kg/s, with corresponding values of 12.91, 11.30, 12.01, and 9.78 at higher flow rates. The TEIF percentage range for Ng = 1, 2, 3, and 4 was 1.93–1.44%, 2.16–1.52%, 1.81–1.23%, and 1.76–1.14%, respectively, indicating the superior performance of Ng = 2. Based on these findings, the present design of solar air heaters can be effectively utilized for air drying processes, offering a sustainable and energy-efficient solution for various industrial and agricultural applications.